Implementasi Metode ANP Untuk Pemberian Bantuan Sosial - Wulandari, Putri; Soelistijadi, R.; Lestariningsih, Endang (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Poverty is a condition of a person or group of people with limited assets and valuables. With these limitations, the community is unable to finance the necessities of a decent life. Standards for the needs of a person’s life worth include food and drink, clothing, a place to live or a house,work and so on. The selection of social assistance recipients is still done manually so that it will affect the outcome of the decision. So, it is necessary to create a system that helps the decision support process for social assistance recipient the ANP (Analytic Network Process) method. In ANP there are 7 (seven) stages, including : determining alternatives, determining criteria, determining alternative comparisons for each node in the criteria cluster, determining the comparison of criteria for each node in the alternative cluster, calculating the weighted supermatrix, calculating the unweighted supermatrix and supermatrix limit. The alternative refers to the name of the community that is the candidate for assistance and the criteria refers to a requirement for social assistace recipients in the Bumirejo sub-district. The first step is calculating ANP by inputting alternative data and criteria data and determining an alternative comparison table for nodes in each criterion cluster and vice versa, in order to produce an index and consistency ratio. The implementation of ANP determines an unweighted and weighted supermatrix with a limit supematrix so as to produce a rangking of decision support system for determining poverty ranking in the provision of social assistance with the lowest synthesis value of 0,11824021. so it can be concluded that this final result can be used as a benchmark for social assistance recipients based on predetermined criteria